Capital Asset Pricing Model and Shariah-Compliant Capital Asset Pricing Model: Evidence from Pakistan Stock Exchange - Rehan, Raja; Chhapra, Imran Umer; Mithani, Salman; Patoli, Abdul Qadir (The journal of contemporary issues in business and government, 2021)
The key objective of this study is to recommend a novel approach in pricing Shariah based financial assets by testing Shariah-Compliant Capital Asset Pricing Models which can potentially replace the conventional CAPM in PSX. Using eighteen years extracted data from Thomson Reuters Data Stream over the period of January 2001 to December 2018 and by deploying Generalized Method of Moments (GMM), this study develops and analyses Shariah-Compliant Capital Asset Pricing Model. The returns of the stocks traded on PSX are calculated through the CAPM equation with Risk-Free Rate, without Risk- Free Rate, Zakat, NGDP and Inflation. The impact of size anomaly is also gauged in the study. The findings are surprising and specify that the Shariah CAPM can be the alternate of the conventional CAPM. The results of this study may show a new way to the investors, corporates and banks to calculate the required rate of returns of their securities.